Phenomenology, neuroscience and “the human”: A forensic and legal perspective - Cassini, Enrico (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2021)
One of the hardest and staunchest viewpoints in the fields of neuroscience and neurophilosophy is that of eliminative materialism, according to which a number of mind-related concepts like thought, consciousness, free will, etc. can easily be dismissed as philosophical or commonsensical illusions. Eliminative materialism, as a matter of fact, aims to absorb a lot philosophical, legal, or anthropological problems in the area of brain functions, often labelling them as “folk psychology”. Is it still possible to think the same concepts and problems, within a neuroscientific approach, avoiding the temptation to reduce them merely to a “ghost” of brain biology? Many philosophers, jurists, and neuroscientists give an affirmative answer. Francisco Varela, both neuroscientist and philosopher, attests that a way to deal with the “hard problem” of consciousness consists in combining the outcomes of neuroscience, with the methods and questions of phenomenology (a strategy recently deepened by Gallagher and Zahavi). Even several legal scholars and forensic scientists (e.g. Ugo Fornari, Andrew Millie, or Aaron Daniels) tend to integrate those methodologies, in order to think mind and human experience maintaining them in a scientific setting. This article defines the opportunity to develop a specific neuro-phenomenological attitude in the realm of legal philosophy and “philosophical criminology” (Millie), to achieve a better understanding of traditional mind-related ideas and problems in a dialogue with neuroscientific thought.